Review on Internet of Things (IOT) in agriculture: limitations and barriers of smart farming in oil palm plantation in Malaysia / Ahmad Safwan Abu Bakar - Abu Bakar, Ahmad Safwan (Faculty of Plantation and Agrotechnology, 2019)
Smart farming or precision farming is not yet fully implemented in oil palm plantation. The component of smart farming includes the usage of wireless internet and Global Positioning System which connected with drone, machinery and equipment without visiting the farm. In some research, smart farming is stated to become the future of agriculture sector in which helps to overcome several problems nowadays. For example, labour shortage for plantation sector will cause the usage of smart farming to be implement in the next 10-15 years. The main of causes for this problem is because of high demand and supply for palm oil product. Oil palm production has brought about unlimited economic profits and currently it is an emerging economic sector in Malaysia. At present, Malaysia accounts for an overwhelming contribution to world's palm oil production and export which is 39% and 44%, respectively.. However the implementation of smart farming is restricted on several factors. This study is attempt to discuss current scenario of limitations and barriers of smart farming on oil palm plantation in Malaysia which causes by weak imperatives for change, interoperability of different standards and connectivity in rural areas.